Identification Bridging of Inter-Community On Social Capital Community Village Empowerment (Case Study: Tulungrejo Village Batu City) - Dekky Fauzi; Maryunani Maryunani; Asfi Manzilati (e-2477-1929, 2020)
The aim of the research is to identify Bridging of Inter-Community on Social Capital Community Village Empowerment between communities that affect the existence of Farmers Group Makmur Abadi (KTMA) with businesses around so it can become social capital that can be converted into economic benefits. The research method is qualitative method of phenomenology. The results showed that bridging (1) role to relate and bridge the cooperation and trust between groups in the Tulungrejo village, (2) improves service coverage and trust (3) price competitiveness by apple jobbers harms the community business climate (4) bridging increases profitability and expands access to resources.The role of bridging social capital is identified in the values of keep the quality; guests are king; business partnership; delay payment and barter; price competitiveness; and figure. The presence of figure values in various group policies has proven help the group facing the socio-economic dynamics so facilitate the conversion of social capital into economic benefits.